2011
DOI: 10.1002/pen.22085
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and thermal degradation of novel poly(2‐(5‐bromo benzofuran‐2‐yl)‐2‐oxoethyl methacrylate)

Abstract: A novel methacrylate monomer containing benzofuran side group, 2‐(5‐bromo benzofuran‐2‐yl)‐2‐oxoethyl methacrylate (BOEMA), was synthesized from esterification reaction of 2‐bromo‐1‐(5‐bromo benzofuran‐2‐yl) ethanone with sodium methacrylate at 85°C in the presence of 1,4‐dioxane solvent. After characterization with Fourier transform infrared spectrophotometer, nuclear magnetic resonance (1H‐NMR and 13C‐NMR), its homopolymerization was carried out by free radical polymerization at 60°C in the presence of benzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The weight loss curves showed that decomposition of poly(BMKMA) took place in one stage in the 30% weight loss area attributed to the formation of volatile hydrocarbons in the first decomposition temperature range up to approximately 270 °C. 13 TGA curves and peak temperatures shift to higher values with an increase in the heating rate. This alteration has been recorded in the a) b) case of thermal degradation of different types of polymers.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The weight loss curves showed that decomposition of poly(BMKMA) took place in one stage in the 30% weight loss area attributed to the formation of volatile hydrocarbons in the first decomposition temperature range up to approximately 270 °C. 13 TGA curves and peak temperatures shift to higher values with an increase in the heating rate. This alteration has been recorded in the a) b) case of thermal degradation of different types of polymers.…”
Section: Resultsmentioning
confidence: 93%
“…13 In order to estimate the thermal degradation mechanism, these functions can be applied to thermogravimetry. 23 …”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Pristine montmorillonite clay, Na-MMT, (cation exchange capacity, CEC = 119 meq/100 g) was purchased from Sigma-Aldrich. Poly(2-(5-bromo benzofuran-2-yl)-2-oxoethyl methacrylate), poly(BOEMA), was synthesized by free radical polymerization at 60 • C in the presence of benzoyl peroxide initiator and 1,4-dioxane solvent and characterized according to reference [36] as seen in Scheme 1.…”
Section: Methodsmentioning
confidence: 99%